2013
DOI: 10.1186/1754-6834-6-72
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis to investigate the high starch accumulation of duckweed (Landoltia punctata) under nutrient starvation

Abstract: BackgroundDuckweed can thrive on anthropogenic wastewater and produce tremendous biomass production. Due to its relatively high starch and low lignin percentage, duckweed is a good candidate for bioethanol fermentation. Previous studies have observed that water devoid of nutrients is good for starch accumulation, but its molecular mechanism remains unrevealed.ResultsThis study globally analyzed the response to nutrient starvation in order to investigate the starch accumulation in duckweed (Landoltia punctata).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 77 publications
7
84
0
3
Order By: Relevance
“…By contrast, previous studies have indicated that duckweed showed huge potential in high-starch accumulation during nutrient starvation (Tao et al, 2013;Xiao et al, 2013). The results of the high-starch accumulation experiment showed that the duckweed dry biomass per square meter increased from 16.31 ± 1.43 g/m 2 to 59.68 ± 0.81 g/m 2 in 11 days, and the average growth rate for 11 days was 3.93 ± 0.90 g DW/m 2 /d, which was lower than that in the wastewater.…”
Section: Accumulation Of High-starch In Duckweedmentioning
confidence: 56%
“…By contrast, previous studies have indicated that duckweed showed huge potential in high-starch accumulation during nutrient starvation (Tao et al, 2013;Xiao et al, 2013). The results of the high-starch accumulation experiment showed that the duckweed dry biomass per square meter increased from 16.31 ± 1.43 g/m 2 to 59.68 ± 0.81 g/m 2 in 11 days, and the average growth rate for 11 days was 3.93 ± 0.90 g DW/m 2 /d, which was lower than that in the wastewater.…”
Section: Accumulation Of High-starch In Duckweedmentioning
confidence: 56%
“…The strains of L. punctata 0202 used in this study were isolated from the ponds of Chengdu, China, as done previously (Tao et al, 2013). Upon collection, the plants were rinsed gently with distilled water to remove debris and then the healthy fronds were placed in plastic aquaria containing Hoagland solution comprised of macronutrients (1 mM KH 2 PO 4 , 10 mM KNO 3 , 2 mM Ca(NO 3 ) 2 , and 2 mM MgSO 4 ), micronutrients (46 uM H 3 BO 3 , 9 uM MnCl 2 .4H 2 O, 0.76 uM ZnSO 4 .7H 2 O, 0.32 uM CuSO 4 , and 0.55 uM H 2 MoO 4 ), and an iron source (78 uM Fe-EDTA).…”
Section: Plant Materials and Cultivationmentioning
confidence: 99%
“…The PCR reactions were performed utilizing Real-Time PCR System iQ5 (Bio-Rad, USA). We designed the primers for LeAPL2, LeAPL3, LeSSS, LeAMY, and LeBMY according to the transcription sequencing data of our previous experiment (Tao et al, 2013), while the primers of LeAPL1 and LeAPS were designed based on the cDNA of LeAP-L1(Genbank accession number KJ603244) and LeAPS (Genbank accession number KJ603243), respectively (Table 1). We performed qRT-PCR with the gene-specific primer pairs listed in Table 1 using the following parameters: 30 s at 95 C, 40 cycles of 5 s at 95 C, and 30 s at 60 C. PCR products were melted by gradually increasing the temperature from 55 to 95 in 0.5 C increments.…”
Section: Quantitative Real-time Reverse Transcription-polymerase Chaimentioning
confidence: 99%
See 2 more Smart Citations